2012
DOI: 10.1111/ipd.12015
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride intake from food items in 2‐ to 6‐year‐old Brazilian children living in a non‐fluoridated area using a semiquantitative food frequency questionnaire

Abstract: This result reinforces the use of the FFQ as a promising alternative to duplicate diet in order to estimate FI in children in this age range, with potential application in broad epidemiological surveys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Daily intakes of fluoride from drinks (water + beverages), foods, and toothpaste for 2- to 12-year-olds children residing in areas with the low, optimal, and high concentrations of F – in drinking water were estimated based on research reported over the past decade (Table ). …”
Section: Fluorine In the Environmentmentioning
confidence: 99%
“…Daily intakes of fluoride from drinks (water + beverages), foods, and toothpaste for 2- to 12-year-olds children residing in areas with the low, optimal, and high concentrations of F – in drinking water were estimated based on research reported over the past decade (Table ). …”
Section: Fluorine In the Environmentmentioning
confidence: 99%
“…Large amounts of fluoride are also found in canned foods. Another issue is the way food is prepared for consumption, including its processing and added ingredients, which ultimately also have a significant impact on the final fluoride content in the supplied food [ 1 , 2 , 42 ]. Cantoral et al paid attention to the amount of fluoride in food, which depends mainly on salt, water, and the packaging utilized in the production process.…”
Section: Sources Of Fluoridementioning
confidence: 99%